Transitional justice and corporate accountability from below : deploying Archimedes' lever / Leigh A. Payne, Gabriel Pereira, Laura Bernal-Bermúdez. - Payne, Leigh A.; Pereira, José Roberto Gabriel, 1977-; Bernal-Bermúdez, Laura, 1985- (Cambridge University Press, 2020)
Bruno Tesch was tried and executed for his company's Zyklon B gas used in Nazi Germany's extermination camps. This book examines this trial and the more than 300 other economic actors who faced prosecution for the Holocaust's crimes against humanity. It further tracks and analyses similar transitional justice mechanisms for holding economic actors accountable for human rights violations in dictatorships and armed conflict: international, foreign, and domestic trials and truth commissions from the 1970s to the present in every region of the world. This book probes what these accountability efforts are, why they take place, and when, where, and how they unfold. Analysis of the authors' original database leads them to conclude that 'corporate accountability from below' is underway, particularly in Latin America. A kind of Archimedes' lever places the right tools in weak local actors' hands to lift weighty international human rights claims, overcoming the near absence of international pressure and the powerful veto power of business.